Dedifferentiation of Asparagus officinalis L. mesophyll cells during initiation of cell cultures - Paul, E.; Harikrishna, K.; Fioroni, O.; Draper, J. (Elsevier, 1989)
Mesophyll cells of asparagus will undergo dedifferentiation when placed in culture medium. Cells may be mechanically isolated from asparagus cladodes rapidly and in sufficient quantities to enable a study of this switch in development at the microscopic level. During dedifferentiation a reproducible, ordered sequence of events occurs that includes revocery from wound stress, reactivation of the cell cycle followed by cell expansion and cell division. Dedifferentiation in vitro is a complicated process which, at the cellular level, appears to resemble most aspects of dedifferentation during callus formation at wound sites in intact plants and large explants. Results from this intial study have been used to define developmental phases of dedifferentiation, which will be used in future molecular analyses of this system.